How to address sustainability at the city level - Barbosa, José Amarilio (2013)
A brief analysis of the environmental, social and economic paradigm of nowadays cities, allows reaching a conclusion: current cities are not sustainable. Considering this, it is very important to study the causes of such unsustainability and to develop models for sustainable cities. There are a limited number of studies in this area, but the scientific community lacks even more studies related to the implementation of these models in current cities. Consequently there is the need to explore this field. This work emerges with the objective of analysing how it is possible to implement sustainability in cities throw the development of a sustainable city model and an urban regeneration plan. The development of sustainable city models is a very complex topic. The analysis of the state of the art shows that one must consider the relation between environmental and social aspects in the development of sustainable cities, while taking special concerns when considering the economic issues. It was also concluded that cities should be subject to performance assessments. It was also demonstrated that a city can only be sustainable if its population behaves in harmony with the city’s sustainability model and that the behavior of a community is determinant in the sustainability level that a model can achieve.